Small RNA Pathways That Protect the Somatic Genome - Hyun, Seogang (Int J Mol Sci, 2017)
Transposable elements (TEs) are DNA elements that can change their position within the genome, with the potential to create mutations and destabilize the genome. As such, special molecular systems have been adopted in animals to control TE activity in order to protect the genome. PIWI proteins, in collaboration with PIWI-interacting RNAs (piRNAs), are well known to play a critical role in silencing germline TEs. Although initially thought to be germline-specific, the role of PIWI–piRNA pathways in controlling TEs in somatic cells has recently begun to be explored in various organisms, together with the role of endogenous small interfering RNAs (endo-siRNAs). This review summarizes recent results suggesting that these small RNA pathways have been critically implicated in the silencing of somatic TEs underlying various physiological traits, with a special focus on the Drosophila model organism.